The Application of Glycolipid-Type Microbial Biosurfactants as Active Pharmaceutical Ingredients for the Treatment and Prevention of Cancer - Aileen M. B. McMahon; Matthew S. Twigg; Roger Marchant; Ibrahim M. Banat (Pharmaceuticals)
Pharmaceutical scientists have researched the potential of secondary metabolites biosynthesized by microorganisms as active pharmaceutical ingredients (APIs) for the treatment of cancer. Ideally, these APIs should possess anticancer bioactivity that specifically targets tumor cells while having little cytotoxic effect on healthy tissue. Biosurfactants are microbial secondary metabolites with surface-active properties and individual bioactivities that have the potential to either destroy cancer cells in a targeted fashion or prevent tumor cell formation. Currently, the best-studied class of microbial biosurfactants for the purpose of anticancer bioactivity is glycolipids, which contain a hydrophilic sugar moiety bonded to a hydrophobic fatty acid. Anticancer investigations are mainly carried out using in vitro models that show that compounds belonging to each of the four sub-classes of microbial glycolipid have significant anticancer bioactivity. The targeted action of this activity appears to be highly dependent on a specific congener molecular structure with nuanced alterations in structure leading to the killing of both tumor and healthy cells. This review compiles the current literature relating to glycolipid anticancer activity and provides a critical appraisal of exploiting the bioactivity of these compounds as novel anticancer agents. Finally, we propose several suggestions on how this research could be improved moving forward via method standardization.